Analysis of Factors Affecting Surabaya Youth's Perception of Surabaya City Branding - Randy Oktavianus Gunawan; Daisy Marthina Rosyanti; Melati Ayuning Pranasari (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2025)
City Branding is an important part of improving competitiveness, attracting investment, and tourists. City Branding is an interesting topic to review especially in the context of marketing the city. This research was conducted to determine the factors that can influence the perception of Surabaya youth towards City Branding of Surabaya City. Data was collected through questionnaires distributed to respondents and processed quantitatively. The method used is validity and reliability analysis, then continued with multiple linear regression Ordinary Least Square (OLS) model connected to descriptive analysis. It can be seen that Media and Information and Experience can be significant factors in shaping the perceptions of Surabaya youth towards Surabaya City branding. Surabaya youth who are often exposed to positive information about the city through various media tend to have a more favorable view of